STUDY OF THE ULTRASOUND EFFECT UNDER HUMORAL IMMUNE RESPONSE (Fiep Bulletin - online, 2015)
Introduction and Objective: the ultrasound enhances the movement of molecules causing: more vibrations, molecular collisions and increasing tha local temperature. The ultrasound therapy is applied to rheumatoidic diseases, helping in healing and reducing the pain. This work has the objective to study antibody response by IgM levels, using ovolbumin (OVA) as the immunogen, in mice with ultrasound therapy. Methods and Results: SWISS mice have been used for the studies. The animal have been dividied in 2 groups of 18 animals each. The first group (untreated) have been inoculated with 180g of OVA on 0,2 mL of PBS, on the 0, 7, 14, 21, 28 days. On the second we repeated the inoculation protocol to the OVA, as set before, and the groups fave received daily an ultrasound therapy in the abdominal region, far 50 seconds each, with intensity of 1w/cm2 (group two) under frequency of 3 MHz, both in continuous mode during 60 consecutives days. All inoculation have been done in the intraperitonial way. The sera of mice have been collected in 7,14,21,28 and 60 days for antibodies of the IgM class, which have been measured in assays by ELISA method. All animals, on the second group have survived until the end of experiment, showing higher titles (mean1259; sd 4,49) of IgM on the 14 than the ultreated group, however this titles (mean 989; sd 2,14) reduced 7 days after that. Conclusion: we concluded that ultrasound therapy anticipates the humoral response and induce down regulation by continued use.
Keywords: Humoral Immune Response; Ultrasound; IgM.